Photographic motifs in Proust's À la recherche du temps perdu - Larkin, Áine (Trinity College (Dublin, Ireland). Department of French, 2007)
This thesis addresses the question of the assimilation of photography into French literary culture in the late-nineteenth and early-twentieth century, specifically in relation to Marcel's Proust's A la recherche du temps perdu. The introduction outlines my understanding of the distinctive characteristics of the photographic system of image production. It briefly outlines the response of French literary writers from 1839 onwards to the appearance and dissemination of photographic practice and the photographic image, and then suggests that Proust's appropriation of photography demonstrates a more profound engagement with this medium than that of writers who preceded him.
Keywords: French, Ph.D.; Ph.D. Trinity College Dublin